The Health and Housing Study: Nutrition-Related Outcomes Among Low- to Moderate-Income Individuals Living in or Seeking to Live in New Subsidized Chinatown-Based Housing. (7th June 2021) - Maafs-Rodríguez, Ana; Pustz, Jennifer; Ismail, Mehreen; Goldman, Laurie; Levine, Peter; Liou, Angie; Chomitz, Virginia
Abstract: Objectives: Housing stability, food security and healthy eating are interrelated. In 2015, a housing lottery for newly developed subsidized housing in Chinatown, Boston, MA was held for low- and moderate- income families who were randomly selected from a waitlist. Four years later (19/20), our study explores the associations between housing status (living in the new subsidized building (NSB) or being on the lottery waitlist) and Food Insecurity (FI); use of food safety net programs (SN), defined as use of SNAP, WIC and/or food pantries; weekly fruit and vegetable consumption (FV); weekly soda consumption; and monthly fast food consumption (FF). Methods: Questionnaire links were sent to NSB ( n  = 95) and waitlist ( n  = 2498) households. Logistic regression was used to explore the association between housing status and (1) FI (2-item screener) and (2) use of SN (self-reported use in the past year). Linear regression with robust standard error estimation was used to explore the association between housing status and weekly consumption of (1) FV, (2) soda, and (3) monthly consumption of FF, (assessed through health behavior questions from the California Health Interview Survey). Models were adjusted for age, sex, ethnicity, household size, education, income, employment status and distance to grocery store. Results: 138 respondents completed the survey; NSB = 36, waitlist = 102. The two housing status groups were demographically similar. Respondents in the NSB showed non-statistically significant lower odds of experiencing FI (OR 0.65, 95% CI [0.3, 1.6]) and of using SN (OR 0.45, 95% CI [0.1, 1.6]). Respondents in the NSB showed non-statistically significant higher weekly consumption of FV (β 2.03, 95% CI [−1.5, 5.6]); lower weekly consumption of soda (β −0.39, 95% CI [−1.9, 1.1]) and lower monthly consumption of FF (β −1.19, 95% CI [−3.9, 1.5]), when compared to respondents on the waitlist. Conclusions: In this small sample, main outcomes were not significantly different. Dietary intakes among NSB residents were consistently positive compared to waitlist residents. Future studies should continue to explore mechanisms through which living in a NSB may impact nutrition and health outcomes. Funding Sources: Tufts Collaborates Seed Grants. Conclusions do not represent any U.S. Department of Agriculture office or Government determination. This research was not part of MI's work at USDA.